2000
DOI: 10.1351/pac200072071357
|View full text |Cite
|
Sign up to set email alerts
|

Frontiers in green chemistry utilizing carbon dioxide for polymer synthesis and applications

Abstract: In the last ten years, there has been incredible growth in research involving the use of carbon dioxide as an environmentally benign solvent. This article will highlight polymer synthesis, characterization, and applications in CO 2 and place this research in the context of both green chemistry and the latest developments in CO 2 technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…

Electrochemical reduction of carbon dioxide (CO 2 ) is a viable solution for conversion of atmospheric CO 2 to value-added materials such as carbon monoxide (CO). [6][7][8][9][10][11] In this respect, electrocatalytic CO 2 reduction reactions (CO 2 RRs) pose a promising alternative to this end. This project exhibits the importance of molecular design in accessing heterogeneous applications with CNTs.

Consumption of fossil fuels for energy production in recent decades has dispensed alarming amounts of carbon dioxide (CO 2 ), one of the leading contributors to climate change, into the atmosphere.

…”
mentioning
confidence: 99%
“…

Electrochemical reduction of carbon dioxide (CO 2 ) is a viable solution for conversion of atmospheric CO 2 to value-added materials such as carbon monoxide (CO). [6][7][8][9][10][11] In this respect, electrocatalytic CO 2 reduction reactions (CO 2 RRs) pose a promising alternative to this end. This project exhibits the importance of molecular design in accessing heterogeneous applications with CNTs.

Consumption of fossil fuels for energy production in recent decades has dispensed alarming amounts of carbon dioxide (CO 2 ), one of the leading contributors to climate change, into the atmosphere.

…”
mentioning
confidence: 99%
“…The CO 2 is easily formed by the oxidation of organic molecules during combustion or respiration. Furthermore, CO 2 can be acquired from natural reservoirs or recovered as a byproduct of industrial chemical processes, so, no new production of CO 2 is necessary and there will be no addition to greenhouse gases (Young et al, 2000). This work presents the successful production of CNTs and CNFs by catalytic decomposition of methane (CH 4 ) and CO 2 over an unsupported nickel alloy catalyst (LaNi 5 ) in a 'modified' SFCCVD reactor (Figure 8) at temperatures ranging from 650-850°C (Moothi, 2009;Maphutha, 2009 It was observed that CH 4 produced well defined CNTs at all the tested temperatures (650-850°C) as shown in Figure 9.…”
Section: Use Of Carbon Dioxide and Methanementioning
confidence: 99%
“…Since CO 2 is a gas at room conditions, its convenient removal from polymeric products is possible without costly drying and solvent removal processes. DuPont has recently announced plans for a major investment in the use of SCF_CO 2 for production of fluorinated polymers, see Young and DeSimone (2000). Single-phase solvents are very important in processes where phase separation, and its consequent capillary forces, is …”
Section: Supercritical Fluids and Polymersmentioning
confidence: 99%